The effect of booklet media on increasing husband support for exclusive breastfeeding among breastfeeding mothers - Lia Arianty; Rita Ayu Yolandia; Irma Jayatmi (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Husband support is a crucial factor in the success of exclusive breastfeeding, yet many husbands have limited knowledge and awareness of its importance. Education through booklets has been identified as an effective way to increase this support. Purpose: To determine the effect of using booklets on increasing husband support for exclusive breastfeeding among breastfeeding mothers at the Cireunghas Public Health Center in 2025. Method: This was a quasi-experimental study with a pre-test and post-test design with a control group, conducted in April 2025. The sample consisted of 30 husbands of breastfeeding mothers. Data were analyzed using an independent t-test. Results: Breast milk production increased from 80 ml (40%) to 120 ml (60%) after the intervention, demonstrating the effectiveness of the intervention in increasing breast milk production. In the intervention group, husband support significantly increased by 53% (from 47% to 100%) after the booklet was provided (p=0.05). Meanwhile, in the control group, support increased by only 7% (from 27% to 33%). These results indicate that the booklet is effective in increasing husbands' understanding and attitudes toward the importance of exclusive breastfeeding. Conclusion: The booklet has been shown to be effective in increasing husbands' knowledge, understanding, and support. Suggestion: It is hoped that husbands will continue to improve their understanding and involvement in supporting exclusive breastfeeding.